Idiosyncratic gesture use in a mother-infant dyad in chimpanzees (Pan troglodytes schweinfurthii) in the wild - Bas van Boekholt; Isabelle Clark; Nicole J. Lahiff; Kevin C. Lee; Katie E. Slocombe; Claudia Wilke; Simone Pika (Animal Cognition)
Abstract One promising method to tackle the question, “In which modality did language evolve?” is by studying the ontogenetic trajectory of signals in human’s closest living relatives, including chimpanzees (Pan troglodytes). Concerning gestures, current debates centre on four different hypotheses: “phylogenetic ritualization”, “social transmission through imitation”, “ontogenetic ritualization”, and “social negotiation”. These differ in their predictions regarding idiosyncratic gestures, making such occurrences a crucial area of investigation. Here, we describe a novel and potential idiosyncratic behaviour — ‘hand-on-eye’ — which was initially observed in one mother-infant dyad in a community of chimpanzees living in the wild. We systematically investigated the form, sequential organisation, intentionality, usage, function, and distribution of the behaviour over a five-year period. The results showed that ‘hand-on-eye’ was nearly exclusively deployed in a single mother-infant dyad, was accompanied by hallmarks of intentionality, and served to initiate or resume joint dorsal travel. Although the behaviour was observed once in each of three other mother-infant dyads, these lacked the same frequency and hallmarks of intentionality. ‘Hand-on-eye’ thus qualifies as an idiosyncratic gesture. The proposed developmental pathway gives support to both the “ontogenetic ritualization” and “social negotiation” hypotheses. It also stresses the crucial need for longitudinal approaches to tackle developmental processes that are triggered by unique circumstances and unfold over relatively long time windows.